(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Innovations and advances in material engineering and surface engineering play a key role in developing modern, safe, durable, and biocompatible implants. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “hip-implants”. All published articles related to “hip- implants” from “Scopus”, were Journal of Bone and Joint Surgery and Journal of Arthroplasty. The leading organization engaged in research regarding hip implants was the University of Leeds. The most active authors who had made valuable contributions related to the surface coating of implants were Jacobs J.J